[Fe–S] biogenesis and unusual assembly of the ISC scaffold complex in the Plasmodium falciparum mitochondrion. Issue 2 (4th June 2021) - Mohammad Sadik,; Mohammad Afsar,; Ramachandran, Ravishankar; Habib, Saman
Abstract: The malaria parasite harbors two [Fe–S] biogenesis pathways of prokaryotic origin–the SUF and ISC systems in the apicoplast and mitochondrion, respectively. While the SUF machinery has been delineated, there is little experimental evidence on the ISC pathway. We confirmed mitochondrial targeting of Plasmodium falciparum ISC proteins followed by analyses of cysteine desulfurase, scaffold, and [Fe–S]‐carrier components. Pf IscU functioned as the scaffold in complex with the Pf IscS– Pf Isd11 cysteine desulfurase and could directly assemble [4Fe–4S] without prior [2Fe–2S] formation seen in other homologs. Small angle X‐ray scattering and spectral studies showed that Pf IscU, a trimer, bound one [4Fe–4S]. In a deviation from reported complexes from other organisms, the P. falciparum desulfurase‐scaffold complex assembled around a Pf IscS tetramer instead of a dimer, resulting in a symmetric hetero‐hexamer [2× (2 Pf IscS–2 Pf Isd11–2 Pf IscU)]. Pf IscU directly transferred [4Fe–4S] to the apo‐protein aconitase B thus abrogating the requirement of intermediary proteins for conversion of [2Fe–2S] to [4Fe–4S] before transfer to [4Fe–4S]‐recipients. Among the putative cluster‐carriers, Pf IscA2 was more efficient than Pf NifU‐like protein; Pf IscA1 primarily bound iron, suggesting its potential role as a Fe 2+ carrier/donor. Our results identify the core P. falciparum ISC machinery and reveal unique features compared with those in bacteria or yeast and human mitochondria. Abstract : The Plasmodium mitochondrial pathway for [Fe–S] assembly is not experimentally explored. We determine targeting of ISC proteins and probe core functions of sulfur mobilization, [Fe–S] assembly and cluster transfer. Two features of the parasite pathway differ from ISC in bacteria and human mitochondria‐‐ PfI scU directly assembles and transfers [4Fe–4S] to recipient apo‐protein without [2Fe–2S] intermediates, and the core desulfurase‐scaffold complex is a symmetric hetero‐hexamer with a Pf IscS tetramer at the core.